Ablation of endothelial Pfkfb3 protects mice from acute lung injury in LPS-induced endotoxemia. (August 2019) - Wang, Lina; Cao, Yapeng; Gorshkov, B.; Zhou, Yaqi; Yang, Qiuhua; Xu, Jiean; Ma, Qian; Zhang, Xiaoyu; Wang, Jingjing; Mao, Xiaoxiao; Zeng, Xianqiu; Su, Yunchao; et al.
Graphical abstract: Abstract: Acute lung injury (ALI) is one of the leading causes of death in sepsis. Endothelial inflammation and dysfunction play a prominent role in development of ALI. Glycolysis is the predominant bioenergetic pathway for endothelial cells (ECs). However, the role of EC glycolysis in ALI of sepsis remains unclear. Here we show that both the expression and activity of PFKFB3, a key glycolytic activator, were markedly increased in lipopolysaccharide (LPS)-treated human pulmonary arterial ECs (HPAECs) in vitro and in lung ECs of mice challenged with LPS in vivo . PFKFB3 knockdown significantly reduced LPS-enhanced glycolysis in HPAECs. Compared with LPS-challenged wild-type mice, endothelial-specific Pfkfb3 knockout ( Pfkfb3 ΔVEC ) mice exhibited reduced endothelium permeability, lower pulmonary edema, and higher survival rate. This was accompanied by decreased expression of intracellular adhesion molecule-1 (Icam-1) and vascular cell adhesion molecule 1 (Vcam-1), as well as decreased neutrophil and macrophage infiltration to the lung. Consistently, PFKFB3 silencing or PFKFB3 inhibition in HPAECs and human pulmonary microvascular ECs (HPMVECs) significantly downregulated LPS-induced expression of ICAM-1 and VCAM-1, and monocyte adhesion to human pulmonary ECs. In contrast, adenovirus-mediated PFKFB3 overexpression upregulated ICAM-1 and VCAM-1 expression in HPAECs. Mechanistically, PFKFB3 silencing suppressed LPS-induced nuclear translocation of nuclear factor κB (NF-κB)-p65, and NF-κB inhibitors abrogated PFKFB3-induced expression of ICAM-1 and VCAM-1. Finally, administration of the PFKFB3 inhibitor 3PO also reduced the inflammatory response of vascular endothelium and protected mice from LPS-induced ALI. Overall, these ﬁndings suggest that targeting PFKFB3-mediated EC glycolysis is an efﬁcient therapeutic strategy for ALI in sepsis.